Between Rome and Byzantium : the golden age of the Grand Duchy of Lithuania's political culture : second half of the fifteenth century to first half of the seventeenth century - Kiaupienė, Jūratė (Lithuanian studies without borders, 2020)
"The focus of this book is the unique socio-political and socio-cultural community of the Grand Duchy of Lithuania in the golden age of the late fifteenth to early seventeenth century. This study analyses the cultural and political impact of the values disseminated in the newly created state, such as the concept of the state itself, its governance, representation, laws, and other elements of the socio-political system. Through theoretical and factographic arguments, this book demonstrates that the Grand Duchy of Lithuania was a social, political, and cultural link between geopolitical and geo-cultural spaces of the Roman West and the Byzantine East. Located at the cultural crossroads of Europe, Lithuania was an ethnically diverse, multilingual, multi-faith, multicultural national space. Nurtured by international contacts, its political system developed rapidly, influencing the formation of geopolitical and geo-cultural mentality of the whole Central Eastern European region"--